Damage Control Laparotomy in Trauma Patients: A Level I Trauma Center Experience - Anthony J. Duncan; Wade A. Hopper; Mentor Ahmeti (Albanian Journal of Trauma and Emergency Surgery)
Introduction: The surgical management of traumatic injury is an evolving and controversial topic. We present outcomes of laparotomy performed for blunt and penetrating trauma at a level I trauma center over a nearly 10-year period.